Profile of conceptual photosynthesis and creative thinking: Study of 7th-grade students - Sumarni, Elis; Setiandi, Anandita Eka; Sunandar, Ari (Biosfer: Jurnal Pendidikan Biologi, 2020)
Profile of students’ creative thinking and conceptual understanding is essential to create an initial description of students’ competencies in overcoming their learning difficulties. The research aims to describe profile of concept understanding and creative thinking skills of 7thgrade students of all SMP Negeri (public junior high school) in Rasau Jaya sub-district, Kubu Raya Regency, West Kalimantan, Indonesia in photosynthesis content. The research uses qualitative descriptive method. The sampling technique employs disproportionate stratified random sampling. Samples consist of 143 students of 7th grade from three SMP Negeri in Rasau Jaya Sub-district, Kuburaya Regency, West Kalimantan, Indonesia. The data collection technique utilizes creative thinking skill test in the form of an essay with fluency, flexibility, originality, and elaboration aspects. Students’ concept understanding test is in the form of four-tier diagnostic test. Data analysis employs descriptive statistics with percentage of creative thinking and conceptual understanding in categories of understanding, partial understanding, misconception, and not understanding. The creative thinking skill percentage of SMPN students in Rasau Jaya, Indonesia in the originality and flexibility aspect is in a fairly creative category, whereas in the elaboration and fluency aspect the category is still less creative. The highest percentage of students’ conceptual understanding is misconception of 45.25% and followed by an understanding of 30.64%, not understand of 13.2%, and partial understanding of 10.97%. The obtained data give evidence that natural sciences (IPA) learning knowledge among junior high school students, especially concept understanding and creative thinking, is still low. Therefore, teachers could develop students’ creative thinking skills so their concept understanding could be improved.